1999
DOI: 10.1590/s0102-311x1999000100004
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos alimentares entre funcionários de banco estatal: padrão de consumo alimentar

Abstract: In order to investigate the health conditions of current employees in a government-owned bank in the State of Rio de Janeiro, we performed a cross-sectional study in two departments where systematic sampling was applied. Among the health conditions, we focused on the employees' eating habit profile using a questionnaire on frequency of food group consumption analyzed through a summary measure (eating score). Although the majority of the study population display good eating habits, the results confirmed a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
11

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
(27 reference statements)
0
8
0
11
Order By: Relevance
“…and also family care (1,3,8,(19)(20) , favours the quality of the food of these workers who are subjected to long hours of professional work. This behaviour pattern, without a shadow of doubt, warrants qualitative studies which could help to understand this relationship´.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and also family care (1,3,8,(19)(20) , favours the quality of the food of these workers who are subjected to long hours of professional work. This behaviour pattern, without a shadow of doubt, warrants qualitative studies which could help to understand this relationship´.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies (20)(21)(22) consider other important factors in relation to overweight and obesity in the female group: the age bracket of the population, characterised in this study as being of middle age, which generates an impact on the metabolism (21) , the condition of already having borne children (20) , marital status (22) and hormonal phenomena such as the climacteric and the menopause (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Results by Fonseca, Chor and Valente 30 and Thompson et al 27 also identified the higher intake of fat and sugar among men. Studies have related the intake of soft drinks with sugar to increasing weight and tooth decays, besides the low use of foods that are sources of calcium 31,32 .…”
Section: Discussionmentioning
confidence: 85%
“…Também Fonseca et al 36 , ao estudarem os hábitos alimentares entre funcionários de um banco estatal reforçam que enfocar, exclusivamente, o beneficio à saúde de mudanças na dieta não é suficiente para alterar os comportamentos alimentares, pois seus efeitos ocorrem em longo prazo e o prazer associado ao ato de comer é imediato. Savio et al 12 , avaliando o almoço servido a participantes do PAT, reforçam que ações voltadas para melhorar as opções alimentares dos trabalhadores devam incorporar uma visão mais holística, considerando as informações técnicas apenas como base para dar conta da situação nutricional corrente em nosso país.…”
Section: Considerações Finaisunclassified